Dynamin 2 Mutants Linked to Centronuclear Myopathies Form Abnormally Stable Polymers - Wang, Lei (American Society for Biochemistry and Molecular Biology, 2010)
Mutations in the dynamin 2 gene have been identified in patients with autosomal dominant forms of centronuclear myopathy (CNM). Dynamin 2 is a ubiquitously expressed ∼100-kDa GTPase that assembles around the necks of vesiculating membranes and promotes their constriction and scission. It has also been implicated in regulation of the actin and microtubule cytoskeletons. At present, the cellular functions of dynamin 2 that are affected by CNM-linked mutations are not well defined, and the effects of these mutations on the physical and enzymatic properties of dynamin have been not examined. Here, we report the expression, purification, and characterization of four CNM-associated dynamin mutants. All four mutants display higher than wild-type GTPase activities, and more importantly, the mutants form high order oligomers that are significantly more resistant than wild-type dynamin 2 to disassembly by guanine nucleotides or high ionic strength. These observations suggest that the corresponding wild-type residues serve to prevent excessive or prolonged dynamin assembly on cellular membranes or inappropriate self-assembly in the cytoplasm. To our knowledge, this report contains the first identification of point mutations that enhance the stability of dynamin polymers without impairing their ability to bind and/or hydrolyze GTP. We envision that the formation of abnormally large and stable complexes of these dynamin mutants in vivo contributes to their role in CNM pathogenesis.